A simple instrument for proxy vector autoregressive analysis - Lukas Boer; Helmut Lütkepohl (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
A major challenge for proxy vector autoregressive analysis is the construction of a suitable instrument variable for identifying a shock of interest. We propose a simple proxy that can be constructed whenever the dating and sign of particular shocks are known. It is shown that the proxy can lead to impulse response estimates of the impact effects of the shock of interest that are nearly as efficient as or even more efficient than estimators based on a conventional, more sophisticated proxy.
Keywords: C32; 330; GMM; heteroskedastic VAR; instrumental variable estimation; proxy VAR; structural vector autoregression